Deep icequakes: What happens at the base of Alpine glaciers?. Issue 3 (5th September 2013) - Walter, Fabian; Dalban Canassy, Pierre; Husen, Stephan; Clinton, John F.
Abstract [1] Basal seismicity cannot be attributed exclusively to glacier stick‐slip motion. As shown by previous studies on temperate Alpine glaciers, there also exist basal seismic sources, which are not due to pure shear mechanisms. Their moment tensors have substantial, if not dominant, isotropic components. Based on first motion data of high‐quality seismic records from Gornergletscher and Triftgletscher, Switzerland, we argue that the observed isotropic components can be explained by tensile faulting. The implied coseismic volumetric change can be both positive (fracture opening) and negative (fracture collapse). We attribute these observations to hydraulic processes near water‐filled cavities, whose connectivity to the subglacial drainage system changes over time. Thus, our proposed icequake source mechanisms cannot be reconciled with pure shear sources at the glacier bed, which would be expected for basal stick‐slip motion. This sliding mode has recently been proposed as a "realitively common" mechanism, which can substantially enhance subglacial erosion. The existence of several seismic source mechanisms (tensile, shear, or some combination of the two) of basal icequakes implies that a solid understanding about the nature of these events is indispensible if conclusions about glacier sliding, subglacial erosion, and other basal processes are to be drawn from observed seismicity.